Refractory Idiopathic Non-Insulinoma Pancreatogenous Hypoglycemia in an Adult: Case Report and Review of the Literature - Then, Cornelia; Nam-Apostolopoulos, Yun-Chung; Seissler, Jochen; Lechner, Andreas (JOP. Journal of the Pancreas, 2013)
Context Non-insulinoma pancreatogenous hypoglycemia is a rare cause of spontaneous hypoglycemia in adults. The ideal diagnostic and therapeutic approach is still controversial, not least because most reported cases lack long-term follow-up. Case report We describe the case of a 58-year-old woman, who was diagnosed with idiopathic non-insulinoma pancreatogenous hypoglycemia in 2001. After resection of 75% of the distal pancreas, she initially experienced no additional hypoglycemic episodes and did not suffer from diabetes mellitus. However, after one month, recurrent hypoglycemia occurred. After resection of the larger part of the remaining pancreatic tissue, the patient suffered from hypoglycemic as well as hyperglycemic episodes. Octreotide and diazoxide were not successful in preventing the hypoglycemic attacks, whereas continuous insulin therapy with an insulin pump helped to stabilize the blood glucose level temporarily. Finally, all remaining pancreatic tissue had to be removed. Conclusion This long-term follow-up of non-insulinoma pancreatogenous hypoglycemia treatment in an adult patient indicates that lateral pancreatectomy may not be sufficient for permanent blood glucose control and emphasizes the need of follow-up data after subtotal pancreatectomy. Image: Standard diagnostic procedure in adults with spontaneous hypoglycemia.